Preliminary studies on the antifertility activity of Averrhoa bilimbi L. - Herrera, C.L; Cuasay, P.M; Ramos, E.V; Chavez, E.P; Dayap, L..A; Rabang, B.C (1986)
This paper involves preliminary studies to verify the previously reported antifertility activity in sows by "kamias" (Averrhoa bilimbi L.) fruit using a modified Female Mouse Fertility Screening Method. Enovid (norethynodrel-mestranol), a commercial drug was used as a positive control while the solvent used to dissolve the test drug was used as negative control. The juice obtained from 5 g, 10 g, and 20 g fresh fruit per kg body weight were tested for antifertility activity and the largest dose equivalent to 14.4 mL/kg reduced the fertility rate of mice by 50% compared with the control. The ethanol extract of the dried fruit produced the same effect at a dose of 1 g/kg. Population experiments on the same extract produced the same results. The butanol fraction of the ethanol extract containing the steroidal glycoside and potassium oxalate gave the same effect at 120 mg/kg dose.